The origin of bedrock depression wetlands in the southern Cape of South Africa: a changing perspective - Ellery, Steven (Rhodes University, Faculty of Science, Department of Geography, 2019)
The predominant theory of the origin of depression wetlands in southern Africa was developed by Goudie and Thomas (1985) and focuses primarily on mechanisms relating to deflation and erosion as the main drivers of wetland formation. This theory is based on wind driven deflation of animal watering areas where heavy grazing and trampling of vegetation promotes removal of sediment over short periods of time by wind, to create local depressions and impoundment of water. However, this theory applies in arid and semi-arid areas where grazing can reduce vegetation sufficiently to lead to deflation but does not fully explain the origins of depression wetlands that have formed in moist climates or on ancient erosion surfaces such as the African Erosion Surface (AES). This study investigates the origin of a depression wetland that has formed on sandstone bedrock through weathering and dissolution on the AES in South Africa. Wetlands like this act as groundwater recharge zones such that water flows away from the centre of the depression, taking with it any dissolved solutes derived from weathering of the bed of the depression. Fluctuations between wet and dry periods create both highly reducing conditions (during wet phases) and highly oxidising conditions (during dry phases) beneath the margins of these depression wetlands. Some of the main constituents of the sandstone in this wetland are iron(III) oxides, which are highly sensitive to redox conditions and have therefore been transported to and trapped in the margins of the depression. The redistribution of iron(III) oxides from the centre towards the margins of the depression has caused a net volume loss in the centre of the depression, causing sagging, and a net volume gain at the margins of the depression associated with swelling. This process occurs over periods upwards of a million years and explains the presence of depression wetlands in moist climates.
Keywords: Wetlands -- South Africa -- Eastern Cape; Geomorphology -- South Africa -- Eastern Cape; Physical geography -- South Africa -- Eastern Cape; Erosion -- South Africa -- Eastern Cape; Evolutionary paleoecology -- South Africa -- Eastern Cape